2005
DOI: 10.1111/j.1365-2044.2005.04336.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of emotional outcomes of intensive care

Abstract: SummaryNegative emotional outcomes (anxiety, depression and post-traumatic stress) have been identified in patients discharged from intensive care. The aims of this prospective, longitudinal study were to assess levels of and changes in emotional outcome after intensive care, and to explore how these relate to objective and subjective indicators of the intensive care experience. Emotional outcome was assessed using the Hospital Anxiety and Depression and Impact of Event Scales. Anxiety (p = 0.046) and depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
170
4
37

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(230 citation statements)
references
References 40 publications
19
170
4
37
Order By: Relevance
“…Such differences may be attributed to the different instruments used to measure PTSD. However, there is a consensus among researchers about the risk factors for the development of symptoms (Cuthebertson, Stracham, & Seatt, 2003;Girard et al, 2007;Rattray, Johnston, & Wildsmith, 2005;Schelling, 2008;Scragg, A. Jones, & Fauvel, 2001), such as being female, going through psychological agitation in the ICU, being restrained mechanically, stopping benzodiazepines during hospitalization, use of opioids for sedation, septic shock, delirium, hypoxia, mechanical ventilation time and prior psychopathology. In these studies, there were no factors that could offer hope of being risk factors such as severity and complexity of neither illness nor hospitalization time.…”
mentioning
confidence: 99%
“…Such differences may be attributed to the different instruments used to measure PTSD. However, there is a consensus among researchers about the risk factors for the development of symptoms (Cuthebertson, Stracham, & Seatt, 2003;Girard et al, 2007;Rattray, Johnston, & Wildsmith, 2005;Schelling, 2008;Scragg, A. Jones, & Fauvel, 2001), such as being female, going through psychological agitation in the ICU, being restrained mechanically, stopping benzodiazepines during hospitalization, use of opioids for sedation, septic shock, delirium, hypoxia, mechanical ventilation time and prior psychopathology. In these studies, there were no factors that could offer hope of being risk factors such as severity and complexity of neither illness nor hospitalization time.…”
mentioning
confidence: 99%
“…Many who show distress will return quickly to normal function and some with a psychological disorder will follow a recovery trajectory [6]. Cross-sectional and cohort studies have reported anxiety and depression conditions in patients recovering from ICU admission at a higher rate than the general population, at between 24% and 45% at six weeks [7], three months [8] and one year [9]after ICU admission. Anxiety and depression conditions often co-exist with posttraumatic stress disorder (PTSD) [10].…”
Section: Recovery From Critical Illnessmentioning
confidence: 99%
“…The aim of patient diaries is to provide ICU survivors with an accurate and informative collection of events, improving the memory recall of factual information. Delusional memories have been associated with anxiety, depression, post-traumatic stress symptomatology [9,12] and poor health-related quality of life [16].The aim of a diary is to provide a coherent narrative of the illness period, clarifying gaps in memory and diminishing the impact or dominance of imagined occurrences and hallucinations [18]. It has also been suggested that diaries can be used by relatives to encourage the healing process, after their own vicarious traumatic experience or as a basis for discussion about the patient's illness experience [10].…”
Section: Icu Diaries To Improve Recovery From Critical Illnessmentioning
confidence: 99%
“…In 2003, Benumof noted the possibility of the epiglottis herniating into the airway tube of the Soft Seal TM (Smiths Medical, Hythe, UK) laryngeal mask [1]. We also want to point out that the design of the Soft Seal mask is different from the LMA-Unique, in particular the distal cuff is thicker (Fig.…”
Section: A Replymentioning
confidence: 99%